BUILDING STUDENTS' MENTAL RESILIENCE IN FACING ACADEMIC PRESSURE - Swandhono, May Agus (International Journal of Multidisciplinary Reseach, 2025)
This study examines the development of mental resilience in students facing academic pressure in higher education settings. Academic pressure has become a significant concern affecting students' psychological well-being and academic performance globally. Using a qualitative approach with phenomenological design, this research explores the lived experiences of 30 undergraduate students from various disciplines at Universitas Yudharta Pasuruan. Data were collected through semi-structured in-depth interviews, focus group discussions, and psychological resilience assessments using the Connor-Davidson Resilience Scale. Findings reveal that students with higher mental resilience demonstrate better stress management, adaptive coping strategies, and sustained academic performance despite challenges. Five major themes emerged: development of adaptive coping strategies, role of social support networks, cultivation of self-efficacy and growth mindset, emotional regulation and stress management, and institutional support mechanisms. Students progressed from maladaptive coping such as avoidance toward problem-focused strategies including time management and help-seeking behaviors. Social support from family, peers, and lecturers proved crucial for resilience development. The study concludes that integrated interventions combining psychological education, peer support programs, emotional regulation training, and compassionate institutional policies can effectively build students' mental resilience, enabling them to navigate academic demands successfully while maintaining psychological well-being